Desain Passive Cooling Menggunakan Perforated Aluminum Plate Pada Fotovoltaik Monokristallin - Sofijan, Armin as (JURNAL SURYA ENERGY, 2020)
The conversion of solar energy into electrical energy using Photovoltaic monocrystalline modules is an alternative power plant that is pollution-free and environmentally friendly. Indonesia is a subtropical area that is rich in sunlight, which is the main raw material for PV. The energy conversion process in PV is strongly influenced by an increase in temperature that exceeds the threshold, which will cause a decrease in PV efficiency. Increasing the efficiency of PV has been done by many researchers from various countries, previous studies mostly used force convection or active cooling methods by adding cooling fans, spray water, heat sinks that require additional energy, problems that arise are how to improve photovoltaic efficiency without adding any extra energies? In this research, increasing the efficiency of PV using the free convection or passive cooling method, designing a perforated aluminum plate that is installed next to the bottom of the PV panel by designing holes 15mm in diameter and 20 mm apart. The idea of this research is something new and has a contribution to science, so it is very necessary to do this research in developing new and renewable technologies.